Analysis of Factors Influencing Student Financial Management - Zahro Fazda Oktavia, Fathimatus; Iqbal Akbar, Dharmawan; Nur Maula, Farisa (DINASTI RESEARCH, 2024)
Financial difficulties are not always caused by the influence of income, but are also influenced by errors in managing finances, for example not planning a financial plan. There are many factors that influence students' financial management behavior. The purpose of this study is to analyze three factors that influence students' financial management, namely financial literacy, self-confidence and the quality of financial learning. The research method used is quantitative descriptive with a population of 83 students of the Accounting Department of the State Polytechnic of Malang in 2023. The results of the study show that financial literacy, self-confidence, and the quality of financial learning have a positive effect on students' financial management, both partially and simultaneously.